3. CSR UNTUK KORBAN KEKERASAN - Naryoso, Agus (Faculty of Social and Political Sciences Diponegoro University, 2008)
CSR (Corporate Sosial Responsibility should be looked as a compound of activities aimed for internal and external stakeholders. The most important thing that offently missed by corporate when planning the CSR activities are understanding the community and its problem in a holictis way. CSR is not about making out something as part of business tren, biut moreover it looks deeply at the social problems arises in the community as well as within the internal part of the company itself. Violence in whatever forms that it takes still become a major public issue in Indonesia as the number of violence against women still quite high. However, none of CSR activities in Indonesia start from this point of view but more just continuing what other companies do and considered as a popular CSR theme to do, for example education, health, enviroment.